Myasthenic Crisis In Pregnancy - David M. French; E. Page Bridges; Matthew C. Hoskins; Charles M. Andrews; Cecil H. Nelson (Clinical Practice and Cases in Emergency Medicine, 2017)
This case reviews the management of a 27-year-old pregnant female in myasthenic crisis. She presented to the emergency department in respiratory distress refractory to standard therapy, necessitating airway and ventilatory support and treatment with plasmapheresis. Myasthenic crisis in the setting of pregnancy is rare and presents unique management challenges for emergency physicians.